The Effect of Solvency and Profitability on Firm Value with Dividend Policy as a Moderating Variable in the Infrastructure Sector for the Period 2020–2024 - Ismi Indrian; Krisdiana (Indonesian Journal Economic Review (IJER), 2026)
This study aims to analyze the impact of solvency and profitability on firm value, with dividend policy as a moderating variable, among infrastructure sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Solvency is measured using the Debt to Equity Ratio (DER), profitability using Return on Equity (ROE), firm value using Price to Book Value (PBV), and dividend policy using the Dividend Payout Ratio (DPR). This study employs a quantitative approach using the Moderated Regression Analysis (MRA) method. The research data was sourced from the companies’ annual financial reports, and 18 companies were selected through purposive sampling, resulting in 90 observations. The results indicate that, partially, the DER does not have a significant effect on PBV with a coefficient of -0.002 and a significance level of 0.550 > 0.05. ROE also does not have a significant effect on PBV with a coefficient of 0.254 and a significance level of 0.548 > 0.05. Meanwhile, DPR has a negative and significant effect on PBV with a coefficient of -0.676 and a significance level of 0.008 < 0.05. The interaction results indicate that DER×DPR has a significant positive effect on PBV with a significance level of 0.002 < 0.05, and ROE×DPR also has a significant positive effect on PBV with a significance level of 0.000 < 0.05. These findings suggest that dividend policy moderates the effects of solvency and profitability on firm value in the infrastructure sector.